Innovative Cell-Based Therapies and Conditioning to Cure RAG Deficiency - Villa, Anna; Capo, Valentina; Castiello, Maria Carmina (Frontiers in Immunology, 2020)
Genetic defects in Recombination Activating Genes (RAG) 1 and 2 cause a broad spectrum of severe immune defects ranging from early severe and repeated infections to inflammation and autoimmune manifestations. A correlation between in vitro recombination activity and immune phenotype has been described. Hematopoietic cell transplantation is the treatment of care; however, the availability of next generation sequencing and whole genome sequencing has allowed the identification of novel genetic RAG variants in immunodeficient patients at various ages, raising therapeutic questions. This review addresses the recent advances of novel therapeutic approaches for RAG deficiency. As conventional myeloablative conditioning regimens are associated with acute toxicities and transplanted-related mortality, innovative minimal conditioning regimens based on the use of monoclonal antibodies are now emerging and show promising results. To overcome shortage of compatible donors, gene therapy has been developed in various RAG preclinical models. Overall, the transplantation of autologous gene corrected hematopoietic precursors and the use of non-genotoxic conditioning will open a new era, offering a cure to an increasing number of RAG patients regardless of donor availability and severity of clinical conditions.